Awareness Programs and Change in Taste-based Caste Prejudice - Ritwik Banerjee; Nabanita Datta Gupta (Institute for the Study of Labor (IZA), 2014)
Becker's theory of taste-based discrimination predicts that relative employment of the discriminated social group will improve if there is a decrease in the level of prejudice for the marginally discriminating employer. In this paper we experimentally test this prediction offered by Becker (1971) in the context of caste in India, with management students (potential employers in the near future) as subjects. First, we measure caste prejudice and show that awareness through a TV social program reduces implicit prejudice against the lower caste and the reduction is sustained over time. Second, we find that the treatment reduces the prejudice levels of those in the left tail of the prejudice distribution - the group which can potentially affect real outcomes as predicted by the theory. And finally, a larger share of the treatment group subjects exhibit favorable opinion about reservation in jobs for the lower caste.
Keywords: C91; O1; J15; 330; caste prejudice; taste-based discrimination; implicit association test; laboratory experiment; media influence